L’agrobiodiversité du dattier (Phoenix dactylifera L.) dans l’oasis de Siwa (Égypte) - Vincent Battesti (Revue d'ethnoécologie)
The date palm (Phoenix dactylifera L.) is certainly the key plant of the oasian ecosystem of Siwa, the only Berber oasis of Egypt, in the Libyan Desert. Nevertheless, its present-day agrobiodiversity still deserves careful study. The agrodiversity of this cultivated plant cannot be addressed without taking into account the local horticultural practices and local ways of categorizing the living. This paper presents the first results of this research.If there is broad consensus on the local Berber names to be used for each part of the plant morphology, establishing a list of the different landraces of date palm in Siwa, in contrast, is far more difficult. It was necessary to clarify the local categorization of this plant and its cultivars. This brought to light two facts: the first, quantitative, is that about fifteen or so named types (cultivars and ethnovarities) exist; the second, qualitative, is that locally the shape does matter, genes matter little. In other words, the resemblance makes the identity, and this has implications on the richness of this resource.To reckon the evolutions of the agrobiodiversity, I had to go through all the literature written about Siwa (since the end of the 18th century) evoking the local named types of the date palm. Combining ethnography with historical analysis of the literature on Siwa points to a quite stable agrobiodiversity over this period. This work also suggests that the local community made some early choices to move not towards a self-sufficient oasis economy, but an economy focused on the export of products of a few elite cultivars. Siwa, with its multi-species cropping system, was perhaps not after all a lost oasis in the sands of the Libyan Desert. This paper is the first step of a two-stage work; the second, within an interdisciplinary research project, will examine samples of these date palms through morphometry of seeds and genetic structure of landrace populations to deepen the analysis of the date palm agrobiodiversity in Siwa, at the North African and Middle Eastern crossroads.